Recurrence of Mitotically Active Cellular Fibroma of the Ovary - Dario Bucella; Jean-Frédéric Limbosch; Frédéric Buxant; Philippe Simon; Isabelle Fayt; Vincent Anaf; Jean-Christophe Noël (Obstetrics and Gynecology International)
Background. 10% of ovarian fibromatous tumours typically exhibit increased cellularity, mitotic activity, and less frequently nuclear atypia. Therefore, the classification within the group of fibromatous tumours may represent some difficulties, thus, one or several of these features should appear. Case. We introduce the clinical and pathologic features based on one case of recurrence of a mitotically active cellular ovarian fibroma (MACF) in the pararectal fossa. This recurrence took place six years after primary surgery. Macroscopically, the tumour was firm, fibrous, well delimited, yellow-white without gross necrosis. On microscopic examination, it was composed of a densely cellular proliferation of fibrolastic-like cells with bland nuclear features and arranged in a fascicular pattern. There was no sign of significant atypia or necrosis. Conclusion. Recently, this case is the first report of a recurrence of MACF, following primary surgery with no tumoral rupture or surgical difficulty. The clinical outcome of ovarian cellular fibromas (CFs) and MACFs is typically uneventful. This case, however, strongly suggests maintaining a long-term clinical follow-up even though the principal tumour was surgically treated without tumour rupture or in the absence of adherence or any surgical difficulty.